EGCG Enhanced the Anti-tumor Effect of Doxorubicine in Bladder Cancer via NF-κB/MDM2/p53 Pathway - Luo, Ke-Wang; Zhu, Xiao-hong; Zhao, Ting; Zhong, Jin; Gao, Han-chao; Luo, Xin-Le; Huang, Wei-Ren (Frontiers in Cell and Developmental Biology, 2020)
Doxorubicin (DOX), the first-line chemotherapy for bladder cancer, usually induces side effects. We previously demonstrated that green tea polyphenol EGCG had potent anti-tumor effect in bladder cancer via down regulation of NF-κB. This study aimed to investigate the additive/synergistic effect EGCG and DOX against bladder cancer. Our results demonstrated that the combined use of DOX and EGCG inhibited T24 and SW780 cell proliferation. EGCG enhanced the apoptosis induction effect of DOX in both SW780 and T24 cells and resulted in significant differences. Besides, EGCG promoted the inhibitory effect of DOX against bladder cancer cell migration. In addition, the in vivo results demonstrated that DOX in combination with EGCG showed the most potent anti-tumor effects among DOX, EGCG and DOX+EGCG treatment groups. Further mechanistic studies determined that the combination of DOX and EGCG inhibited phosphorylated NF-κB and MDM2 expression, and up-regulated p53 expression in tumor, as assessed by western blot and immunohistochemistry. Western blot in SW780 cells also confirmed that the combined use of EGCG and DOX caused significant increase in p53, p21 and cleaved-PARP expression, and induced significant inhibition in phosphorylated NF-κB and MDM2. When NF-κB was inhibited, the expression of p53 and p-MDM2 were changed, and the combination of DOX and EGCG showed no obvious effect in transwell migration and cell viability. In conclusion, the novel application of chemotherapy DOX and EGCG demonstrated potent anti-tumor, anti-migration and anti-proliferation effects against bladder cancer. EGCG enhanced the anti-tumor effect of DOX in bladder cancer via NF-κB/MDM2/p53 pathway, suggesting the potential clinical application against bladder cancer patients.